The effect of pixel size on the accuracy of orthophoto production - Kulur, S.; Yildiz, F.; Selcuk, O.; Yildiz, M. A. (Copernicus GmbH, 2016)
In our country, orthophoto products are used by the public and private sectors for engineering services and infrastructure projects, Orthophotos are particularly preferred due to faster and are more economical production according to vector digital photogrammetric production. Today, digital orthophotos provide an expected accuracy for engineering and infrastructure projects. In this study, the accuracy of orthophotos using pixel sizes with different sampling intervals are tested for the expectations of engineering and infrastructure projects.
Keywords: Technology; Artificial intelligence; Environmental Engineering; Economics; Macroeconomics; Ocean Engineering; photogrammetry; Orthorectification; Filter (signal processing); remote sensing; Engineering; Geometric Processing of Remote Sensing Imagery; Orthophoto; Applied optics. Photonics; Production (economics); geographic information systems; orthophoto; FOS: Environmental engineering; Geology; FOS: Earth and related environmental sciences; Sampling (signal processing); Engineering (General). Civil engineering (General); D Geospatial Modelling Techniques; Computer science; TA1501-1820; Earth and Planetary Sciences; Photogrammetry; Physical Sciences; Environmental Science; Mapping Forests with Lidar Remote Sensing; Computer vision; Pixel; TA1-2040; Geopositioning Accuracy